Strengthening Human Resources to Enhance Competitiveness Using SWOT Analysis - Borman, Restutanti; Natsir, Syahir; Hasanudin, Bakri; Muzakir (Research Horizon, 2025)
Human resource management is a key factor in service industries, as employee competence, motivation, and professionalism directly affect service quality and organizational performance. Effective Human resource practices, including structured recruitment, continuous training, performance management, and reward systems, not only enhance productivity but also strengthen organizational culture and employee commitment. This study aims to identify the strengths, weaknesses, opportunities, and threats in Human resource management, analyze the organization’s strategic position using Internal Factor Evaluation and External Factor Evaluation, and formulate strategies to improve service quality. A descriptive qualitative approach was used, with purposively selected informants, including leaders, Human resource managers, and senior employees. Data were collected through in-depth interviews, observations, and documentation, then analyzed interactively using the Miles and Huberman model and supplemented with SWOT analysis. Findings show that internal strengths, such as a supportive work environment, strong leadership-employee relationships, and employee loyalty, can be leveraged to exploit external opportunities, including market growth and supportive policies. Recommended strategies include promotional initiatives, performance-based rewards, structured recruitment, and regular training. The study concludes that effective Human resource management is essential for creating a competent, motivated, and service-oriented workforce, aligning internal capabilities with external opportunities, and sustaining a competitive advantage in dynamic service industries.